1959
DOI: 10.1172/jci103921
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Excretion in Virilizing Adrenal Hyperplasia *

Abstract: Sodium depletion with concomitant dehydration occurs as a complicating factor in approximately one-third of patients with virilizing adrenal hyperplasia (1). A number of writers have discussed certain differences between the electrolyte disturbance occurring in this syndrome and that of Addison's disease (2-5) and several hypotheses have been offered to explain the sodium loss and potassium retention which occur (1, 4, 6, 7). Although the role of aldosterone is pertinent in many of these hypotheses, the only r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
1

Year Published

1960
1960
1969
1969

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 12 publications
0
9
1
Order By: Relevance
“…Furthermore, the high aldosterone excretion in the nonsalt losers led these authors to suggest that a"sodium-losing" factor was produced by the adrenals of the patients with adrenal hyperplasia, but that compensation occurred only if aldosterone could be secreted above the normal level. The data mentioned above (17) did not confirm earlier results of Prader, Spahr, and Neher (18), but generally agreed with studies published later by De Graeff and Moolenaar (19) and Mattox, Hayles, Salassa, and Dion (20).…”
contrasting
confidence: 62%
See 1 more Smart Citation
“…Furthermore, the high aldosterone excretion in the nonsalt losers led these authors to suggest that a"sodium-losing" factor was produced by the adrenals of the patients with adrenal hyperplasia, but that compensation occurred only if aldosterone could be secreted above the normal level. The data mentioned above (17) did not confirm earlier results of Prader, Spahr, and Neher (18), but generally agreed with studies published later by De Graeff and Moolenaar (19) and Mattox, Hayles, Salassa, and Dion (20).…”
contrasting
confidence: 62%
“…In previous studies on aldosterone excretion in patients with congenital adrenal hyperplasia (17)(18)(19)(20), conclusions were drawn on the assumption that aldosterone excretion is proportional to its secretion. This assumption is not always valid (25), but it seems to be generally justified in congenital adrenal hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Blizzard, Liddle, Migeon, and Wilkins (27), in a comprehensive study of normal children and children with salt-losing and simple virilizing adrenal hyperplasia, found that when salt was restricted normal children and simple virilizers showed an increase in aldosterone excretion, but salt losers did not.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion reached by most of the research investigations (16,(26)(27)(28)(29)(31)(32)(33)(34)(35) is that an aldosterone deficiency does exist in congenital hyperplasia of the salt-losing variety, but not in the simple virilizing form.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation